A study on prevalence of carotid artery stenosis in acute ischaemic stroke patients in Amalapuram, Andhra Pradesh, India - Bharathi, Bonthu Mamatha; Gullapalli, Raveena (International Journal of Research in Medical Sciences, 2019)
Background: Extra cranial carotid disease due to arteriosclerosis is usually associated with hypercholesterolemia and hyperlipidemia. Extra cranial carotid stenosis has been found to be less prevalent in black American and in Egyptians while intracranial disease is far more common Various methods includes transcranial doppler (TCD) ultrasonography, cerebral angiography, computed tomography angiography (CTA) and magnetic resonance angiography (MRA). Methods: All patients with ischaemic stroke of acute onset admitted in the medical wards of Konaseema institute of medical sciences between June 2018 and January 2019 were included in the study. All patients were subjected to CT scan brain study and colour Doppler study of extra cranial carotid arteries and vertebral arteries. Systolic and diastolic velocity of blood flow, carotid intimal medial thickness, presence of athermanous plaque and thrombus was looked for and then the percentage of stenosis of the affected arteries was calculated. Results: In the present study 0ut of 23 patients with carotid stenosis 9 patients had mild carotid stenosis, 8 patients had moderate stenosis and 6 patients had severe stenosis. Out of 23 patients with carotid stenosis the 11 patients have stenosis in the right carotid and 12 patients had stenosis in the left side. The site of stenosis is ICA in 17 patients and CCA in 6 patients. Conclusions: In present study every patient with carotid artery stenosis had one or the other risk factor for carotid atherosclerosis. In other words, there was no patient with carotid artery stenosis, without any risk factor in present study. Hence asymptomatic patients with these risk factors should be screened for carotid stenosis to prevent stroke.